Integrated Community Food Production. A Compendium of Climate-resilient Agriculture Options - Gonsalves, Julian Francis (2016)
This compendium of best practices brings together practical ecologically sound and nutrition-sensitive approaches to improving the productivity of backyard, community and family farms. With the increasing awareness of the importance of safe and healthy diets, there is a resurgence of interest in these complementary pathways to household level food security Many of these ideas are not scale neutral and therefore best done on small scale systems. The opportunities for diversification and intensification are often greater in these backyard and family centered systems. Most of these small scale production systems can quickly be transformed to chemical-free systems of production. This compendium has four main sections: the first section is an Overview chapter which provides a conceptual understanding of the value of agro ecological approaches. It has articles on climate smart agriculture approaches which IIRR has been promoting as part of its engagement with the global CCAFS network and the Philippine Department of Agriculture AMIA 2 Program. The second section is on Intensive Organic Gardening. This section includes the very best of the articles that IIRR has produced in its Bio Intensive Gardening program which it has adapted and refined over three decades and now being promoted nationally through the Department of Education of the Philippine government. The IDRC Canada (and earlier, UNICEF) has been a big supporter of this approach. The bio-intensive gardening program includes a tree component that helps create a micro climate in gardens that lowers the ambient temperatures by 2-3 degrees. Its emphasis on diversity helps turn these gardens into focal points for conserving vegetable diversity. Ways to enhance the nutrition contributions of gardens receive special consideration. This section on organic gardening is comprehensive and, can serve as the basis for designing a training program and field level interventions. The third section is on Family Farming. Here IIRR has relied on its own experiences as well that of other agencies (UPLB, Phil Rice, MBRLC, PRRM, World Neighbors and others) which have contributed articles to previous source books. Crop production is emphasized mostly those relying on regenerative agriculture approaches. Special efforts were made to include climate-smart agriculture ideas (agroforestry, conservation agriculture, mitigation opportunities in agriculture etc). Diversification and sustainable diversification characterizes the approach to family farming. The fourth section is on Small Livestock and Fish Production. Small scale livestock and fish production systems are highlighted in this section. The concern about hormones and antibiotic use in meat production is surfacing as a major health concern. Rural communities can meet their own needs (or even supply local markets) with animals produced in backyards and small farms. Alternative (improved) feeding systems are highlighted in this section (e.g. pig rations formulated from locally secured products). Low cost housing can help reduce the impacts of rising temperatures on livestock and along with small fish production systems, can contribute to enhancing protein requirements of families. Organic meat creates special niche market opportunities for the small producer. This compendium highlights ways of producing food with a small carbon foot print. Diverse systems of food production are environmentally sound and as long as climate change remains a threat, there will be a role for these systems. Moreover, as long as a third of the population (in developing countries) remains poor, and malnourishment prevails, there will be a special role for community level food production. This compendium features one hundred simple ideas each of which, in a small way, can contribute to climate-smart and nutrition-smart ways of producing food.